2020
DOI: 10.1097/md.0000000000022362
|View full text |Cite
|
Sign up to set email alerts
|

Association of cytokine gene polymorphisms with chronic hepatitis C virus genotype 1b infection in Chinese Han population

Abstract: Cytokines are extensively involved in the process of hepatitis C virus (HCV) infection and take a crucial part in host immune regulation. We aimed to explore the potential correlation of cytokine single nucleotide polymorphisms (SNPs) with HCV susceptibility and response rate of interferon (IFN)-based antiviral therapy in Chinese Han population. A case–control genetic association study was conducted between 198 patients with chronic HCV genotype 1b infection and 142 healthy controls. Genetic polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(34 reference statements)
0
4
0
1
Order By: Relevance
“…However, these findings are in contrast to several other studies. A study conducted on chronic HCV infection patients in a Chinese Han population did not observe any significant association between the gene polymorphism of IL-10 rs1800871 and susceptibility to HCV infection [18]. Conversely, they found that the gene polymorphism of rs1800871 played a significant role in patients' response towards antiviral therapy.…”
Section: Discussionmentioning
confidence: 92%
“…However, these findings are in contrast to several other studies. A study conducted on chronic HCV infection patients in a Chinese Han population did not observe any significant association between the gene polymorphism of IL-10 rs1800871 and susceptibility to HCV infection [18]. Conversely, they found that the gene polymorphism of rs1800871 played a significant role in patients' response towards antiviral therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Overall, 32 studies with a total of 5943 HCV cases (NR: 3380; SVR: 2563) and 2697 controls were included in the present study. 4 8 , 17 43 Included studies characteristics are summarized in Table 4 . Twenty-three studies were included for the rs1800896 (-1082 A/G) SNP, 4 8 , 17 , 19 , 22 26 , 29 37 , 39 , 41 17 for the rs1800871 (-819 C/T) SNP, 4 7 , 19 , 22 ,…”
Section: Resultsmentioning
confidence: 99%
“… 4 8 , 17 43 Included studies characteristics are summarized in Table 4 . Twenty-three studies were included for the rs1800896 (-1082 A/G) SNP, 4 8 , 17 , 19 , 22 26 , 29 37 , 39 , 41 17 for the rs1800871 (-819 C/T) SNP, 4 7 , 19 , 22 , 27 , 30 …”
Section: Resultsmentioning
confidence: 99%
“…Otro factor que condiciona la respuesta al tratamiento y evolución de las enfermedades, es el factor genético (17). Estudios realizados en China establecieron que el gen IL28B representa un factor predictivo importante en la respuesta a tratamientos basados con IFN en pacientes infectados con el VHC 1b (18). Öksüz y col., reportaron una relación estadísticamente significativa entre el gen IL28B y el receptor tipo Toll 2 (TLR2) en pacientes infectados con VHC con manifestaciones de fibrosis; concluyendo que juntos son biomarcadores predictivos de enfermedad severa en pacientes con VHC (19).…”
Section: Discussionunclassified